Chagas Disease Expands Its Epidemiological Frontiers From Rural to Urban Areas - Alarcón de Noya, Belkisyole; Díaz-Bello, Zoraida; Ruiz-Guevara, Raiza; Noya, Oscar (Frontiers in Tropical Diseases, 2022)
The infection with the hemoflagellate parasite Trypanosoma cruzi originates from America where the wildlife cycle remains to alternate between mammals and hematophagous triatomines. Transmission through contamination of the bite site by vector feces containing highly infectious forms of parasite or direct ingestion of T. cruzi-infected triatomines appear to be the dominant transmission mechanisms. Man joins the transmission when he enters this wild environment or takes the leaves of palms carrying vectors to build houses. Rural Chagas disease develops associated with populations of low economic resources, with infection and reinfection of vector bites since childhood, and the consequent evolution toward chronic cases in adults, when there is little therapeutic benefit to infected people. The progressive migration of people from rural to urban areas and the adaptation of vectors to the peripheries of cities due to displacement caused by deforestation or urbanization that has favored the presence of enzootic cycles with Panstrongylus geniculatus as the most widely distributed species and mammals (synanthropic and domestic) allow vector transmission by ingestion of food contaminated with excrements containing infectious trypomastigotes as the dominant transmission mechanism in the urban environment. Human-to-human transmissions through vertical mother–child infection, transfusions, organ transplants, and the possibility of sexual transmission, transform the epidemiology and the clinical evolution of Chagas disease in the urban environment. Vectors of American trypanosomiasis are no longer restricted to the endemic area, but its presence has been demonstrated in nonendemic areas of the United States, Asia, and other latitudes. The worldwide plague of bedbugs (Cimex lectularius) threatens the possibility of expansion of transmission since they are vectors susceptible to infection, transmission to mammals, trans-stadial penetration, and not being affected by T. cruzi infection at least experimentally. These factors, added to the presence of an unknown number of migrating Latin American asymptomatic carriers together with the presence of triatomines in other continents, have initiated the globalization of a pathology originating in the American continent. Only with an integrative approach, based on new and better tolerated and efficient drugs, vaccines and residual action insecticides, all of them included in an epidemiological surveillance program.